Answer:
8.3 -8.7n
Explanation:
Maybe you want to simplify this expression.
First of all, recognize it is a sum of four terms. We use "sum" in the general sense, where the things being added can be positive or negative.
3.3
-5.7n
-3n
5
Two of these terms are regular decimal numbers: 3.3 and 5. They can be added together without any fuss: 3.3 +5 = 8.3.
The other two terms are products. One of the factors of the product is a constant, called the "coefficient" of the term. The other factor is the letter n, called a "variable".
You may recall that multiplication is a way to write repeated addition:
3×6 = 6 +6 +6
The factor 3 in this example tells you how many times 6 is included in the sum. We can combine such sums:
(3×6) + (2×6) = (6 +6 +6) +(6 +6) = (3+2)×6 = 5×6
If you replace 6 with n, the same thing is true:
3n +2n = (3+2)n = 5n
That is, we can combine terms containing n by adding their coefficients.
__
Your simplification problem then can be written as ...
3.3 -5.7n -3n +5
= (3.3 +5) +(-5.7n -3n) . . . . . . "like" terms are grouped together
= 8.3 +(-5.7-3)n
= 8.3 -8.7n